Crystallographic Texture and Grain Refinement in the CuCr Alloy Deformed by SPD Method - A. Urbańczyk-Gucwa; A. Brzezińska; B. Adamczyk-Cieślak; K. Rodak (Archives of Metallurgy and Materials, 2019)
Microstructure and texture of the CuCr0.6 alloy processed by rolling with cyclic movement of rolls (RCMR) at room temperature were investigated. The RCMR processing was applied for the samples in different initial conditions in the solid solution followed by quenching into iced water at 1000oC for 3 h and in aging treatment conditions performed at 500oC for 2 h and at 700oC for 24 h. Application of the solution and aging processes prior to RCMR deformation results in the partial dissolution of Cr particles into the Cu matrix and precipitation of the second phase particles. RCMR processing with value of the total effective strain (εft) of 5 was introduced to the material. It was found that the RCMR method is effective in texture weakening. The obtained results revealed that there is a large similarity in texture orientations after RCMR processing independently of heat treatment conditions. Cyclic character of deformation leads to an incomplete transition of LAB to HAB.